Allergic Conjunctivitis - Muhammed Vally; M O E Irhuma (South African Family Practice, 2017)
Allergic conjunctivitis is a condition characterized by conjunctival inflammation caused by airborne allergens. The symptoms include: itching, excessive lacrimation, discharge, and conjunctival hyperaemia pink eye). The disease usually affects young adults and is associated with other allergic conditions like allergic rhinitis, and bronchial asthma for example. There are three types of allergic conjunctivitis, namely acute allergic conjunctivitis, seasonal allergic conjunctivitis (SAC) and perennial allergic conjunctivitis (PAC). The diagnosis is primarily clinical and the prevalence is on the increase. Therapeutic modalities include a combination of topical vasoconstrictor and antihistamine therapies, topical antihistamines with mast cell stabilising properties, topical mast cell stabilisers, topical glucocorticosteroids and (in some cases) oral antihistamines when necessary.